PELESTARIAN SUBAK MELALUI PEMBERDAYAAN ANGGOTANYA DALAM PEMBUATAN PAKAN TERNAK SAPI BALI ALTERNATIF KOMBINASI JERAMI PADI DAN BATANG PISANG SECARA FERMENTASI - Simpen, I. N.; Sutha Negara, I. M.; Dwi Adhi S., N.G.A.M.; Arsa, M.; Arpiwi, N.L. (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
The activity in Subak Dangin Alas Desa Lodtunduh Ubud, to be aim for producing woof of bali cattle alternative by fermentation of mixture banana culm and rice straw which has been carried out from May to September. The activity of subscribers of subak sustainability and continuesly, it is expected to impact on maintenance of the subak in its village. In this activity, have been done survey, producing of cattle woof alternative, socialized, training, accompanying and giving woof to their cattles. In producing of woof of bali cattle, it was done by cutting byproduct of banana culm and rice straw to be size 3-5 cm, then dried 1-2 days for reducing water content and then the fermentor (active microorganism and molasses) and mixture of rice and bran are distributed on its byproduct. The final step, it has been done fermentation for minimum 7 days. The activity result, subscribers of subak were very anthusiastic. Generally, participants have yet to understand detail procedure to make cattle woof alternative which is healthful, natural and preserve by fermentation, so that the application of technology is useful. The cattles may consume its fermentation product.
Keywords: subak, banana culm, rice straw, cattle woof, fermentation